Best music writing 2010 - Powers, Ann; Carr, Daphne (Cambridge, MA : Da Capo Press, 2010)
The eleventh book in the acclaimed series celebrating the best writing on every style of music, from rock to hip-hop, R&B to jazz, pop to blues, and more.
""The Revolution Will Be Harmonized""""The Orange Line Revolution""; ""One on One with Maria Schneider""; ""Conducting 101""; ""Drake""; ""50 Cent""; ""Regret, Divorce, Compromise""; ""The Fighter""; ""A Very Dylan Christmas""; ""Appropriate for Destruction""; ""Help from His Friends""; ""Another Love TKO""; ""Letâ€?s (Not) Get It On""; ""Lady Gaga in Hell""; ""Phil Ochs Greatest Hits""; ""Adamâ€?s Return""; ""Voice of the Century""; ""Vanishing Act""; ""Other Notable Music Writing of 2009""; ""List of Contributors""; ""Credits""
Description based upon print version of record.
English
Description based on print version record.
Keywords: Music -- 21st century -- History and criticism